Caring in the time of COVID-19, longitudinal trends in well-being and mental health in carers in Ireland: Evidence from the Irish Longitudinal Study on Ageing (TILDA). - Mc Garrigle, Christine; Ward, Mark; Kenny, Rose; O'Halloran, Aisling (My University, 2022)
Background: The COVID-19 pandemic in 2020 resulted in the older population being asked to remain at home and avoid other people outside their household. This could have implications for both receipt and provision of informal caring. Objective: To determine if informal care provision by older carers changed during the first wave of the COVID-19 pandemic from pre-pandemic care and if this was associated with a change in mental health and well-being of carers. Design and setting: Longitudinal nationally representative study of community dwelling adults from The Irish Longitudinal Study on Ageing (TILDA) (Waves 3-COVID-Wave 6). Methods: We studied a cohort of 3670 adults aged ≥60 in Ireland during the COVID-19 pandemic (July-November 2020) and compared with previous data collections from the same cohort between 2014-2018. Independent variables were caregiving status and caregiving intensity, outcome measures included depressive symptoms (CES-D8), Perceived Stress (PSS4) and Quality of life (CASP12). Mixed models adjusting for socio-demographics and physical health were estimated. Results: Caregiving increased from 8.2% (2014) to 15.4% (2020). Depression, and stress scores increased while quality of life decreased for all participants. Carers reported poorer mental health, and higher caring hours were associated with increased depression and stress and decreased quality of life scores on average, and increased depression was higher for women. Conclusions: Informal caregiving increased during the pandemic and family caregivers reported increased adverse mental health and well-being and this continued throughout the early months of the pandemic. The disproportionate burden of depression was highest in women providing higher caring hours.
PUBLISHED
Keywords: Caring, Ageing, COVID-19, Quality of life, Depressive symptoms, Perceived stress; Ageing